The Influence of Moral Disengagement and Peer Support on Cyberbullying Behavior - Astuti, Dwi; Suwandi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the influence of moral disengagement and peer support on cyberbullying behavior among adolescents. The population in this study are all adolescents who have Instagram accounts and are in the adolescent development stage in the Jabodetabek area. The research sample consisted of 78 adolescents aged 15-18 years who actively use Instagram social media accounts. The data collection method was conducted through an online survey using a questionnaire distributed randomly to teenagers in the Jabodetabek area. Data processing was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis through Smart PLS software. The results showed that moral disengagement has a significant influence on cyberbullying behavior. Adolescents with high levels of moral disengagement tend to have more frequent cyberbullying behavior. Furthermore, this study also found that peer support has a significant effect on cyberbullying behavior. In this case, positive social support from peers can reduce the tendency of cyberbullying behavior, while negative support can actually increase this behavior. This study provides new insights into the factors that influence cyberbullying behavior among adolescent Instagram users. The findings can be used as a basis for the development of interventions aimed at reducing cyberbullying behavior among adolescents, as well as providing recommendations for relevant stakeholders to design effective prevention programs